Absence of differential predation on rats by Malaysian Barn Owls in oil palm plantations - Puan, Chong Leong; Goldizen, Anne W.; Hussin, Mohamed Zakaria; Mohd Noor, Hafidzi; Baxter, Greg S. (Raptor Research Foundation, 2011)
Barn Owls (Tyto alba javanica) have been widely introduced in Malaysian oil palm plantations to control rodent pests. However, their effectiveness in regulating rodent populations is unknown. We investigated whether Barn Owls selected prey with respect to size and sex classes based on data from 128 pellets of Barn Owls compared to 1292 live-trapped rats in an oil palm plantation in Malaysia. The birds mostly fed on Rattus rattus diardii, the most commonly trapped species. Body mass of prey consumed was predicted based on models derived from measurements from trapped rats. Sex of prey was determined by pelvic measurements with reference to those taken from specimens of known gender. There was no clear selection of prey by Barn Owls in relation to size or sex of prey, and no difference in the body mass of prey between the owls' breeding and nonbreeding seasons. The absence of differential predation in Barn Owls may partly explain the lack of clear evidence that they regulate rodent populations and thus act as successful biological control agents.